Gaya Kepemimpinan Donald Trump dalam Kebijakan Deferred Action for Childhood Arrivals (DACA) pada Dreamers - Arini, Putrima; Moenir, Haiyyu Darman; Harza, Zulkifli (Palito, 2025)
The United States is the country with the highest immigrant population in the world, comprising 13.6% of its total population. The Deferred Action for Childhood Arrivals (DACA) policy, introduced by former President Barack Obama, was a measure aimed at reducing the number of illegal immigrants in the U.S. A significant majority of DACA recipients, approximately 81%, are originally from Mexico. Donald Trump sought to rescind the DACA policy established by Obama. This study aims to examine Donald Trump's leadership style in the context of the DACA policy rescission and its potential impact on international relations and the global image of the U.S. Trump perceived the presence of immigrants as an obstacle to his efforts to enhance the well-being of native-born Americans, necessitating measures to curb immigration in the U.S. The repeal of DACA faced opposition from various parties, who viewed it as a violation of human rights and financially detrimental to the U.S. Trump's role in the rescission of the DACA policy is analyzed using the conceptual framework of "Leader Trait Analysis" by Margaret G. Hermann, et al. This framework identifies three components as parameters of Trump's leadership style and dominance: reaction to political constraints, openness to information, and motivation for action. Based on the operationalization of these concepts, it is concluded that Trump opposed political constraints and disregarded all input and information presented to him in the process of repealing DACA. Furthermore, it was found that Trump was motivated by his priority to enhance the welfare of native-born Americans. Thus, it can be concluded that Trump exhibits a crusader, directive, and goal-driven leadership style.